A first assessment of particle flux over the South Brazil Bight continental slope - Tura, Pedro Marone (2020)
The vertical export of particulate material, especially the particulate organic carbon (POC), is a key component of the oceanic biological pump, which regulates the distribution of elements associated with the primary production of phytoplankton in the upper euphotic zone. To better understand the role of the oceans in future climate change scenarios, it is necessary to comprehend the processes that regulate the magnitude and variations of POC flux among distinct oceanic domains, including the boundaries between continental margins and oceanic basins. This work aims a first assessment of particle flux over the South Brazil Bight continental slope, a tropical western boundary system dominated mainly by the Brazil Current. Total mass flux, and specific carbon, nitrogen and biogenic silica fluxes were measured periodically by two sediment traps installed in the 900 m and 2000 m isobaths, from November 2016 to September 2017. Traps were positioned at 450 m and 750 m deep, respectively. Due to strong contribution of advected particles, high and extremely irregular fluxes were registered at the 900 m isobath (mean = 1.1 g m-2 d-1, Stand. Dev. ± 2.9 g m-2 d-1). The captured sediment suggests the sediment trap was affected by gravity flows, which preclude the estimation of the biological pump contribution over this isobath. It is discussed how gravity flows interfere with the biogeochemical cycle over the continental slope. Over the 2000 m isobath, the POC flux (3.7 mg m-2 d-1; ± 2.5 mg m-2 d-1) followed the seasonal pattern of primary production measured by satellite. POC flux was strongly correlated with biogenic silica content (r = 0.79; p <0.01). This ballast mineral was more efficient than CaCO3 in transferring carbon from the base of the euphotic zone to 750 m. Intra-seasonal variations were related to Brazil Current instabilities, causing the nutricline uplift to higher light levels of the euphotic zone over the shelf edge. Measurements of 15N suggest that higher POC flux occurred during nitrate-based production regimes. The exponential production model F (z) = F750 (z / 750) -b was adjusted, and a mean exponent b = 1.4 (± 0.3) was found. Although initial, the results of this work allow us to estimate that 2.26 x 1012 g C is exported annually over the South Brazil Bight.